2022
DOI: 10.1039/d1ta08092j
|View full text |Cite
|
Sign up to set email alerts
|

Amidinium additives for high-performance perovskite solar cells

Abstract: Perovskite solar cells (PSCs) have developed rapidly and achieved power conversion efficiencies (PCE) of over 25% with diverse technical routes. However, defect is a major factor for device degradation, so...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…On the other hand, if the annealing procedure is conducted under the nitrogen flow, which can quickly cool down the film temperature via thermal convection, the grain size is remarkably reduced (Figure S8). These results imply that expediting the conversion of intermediates into perovskite is crucial for achieving large‐sized polycrystals [19,39] . The X‐ray diffraction (XRD) spectra of the three samples are summarized in Figure 3d, which exhibit a similar profile with two main diffraction peaks around 14.7° and 29.1°, as is characteristic of the tetragonal phase of CH 3 NH 3 PbI 3 polycrystals.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…On the other hand, if the annealing procedure is conducted under the nitrogen flow, which can quickly cool down the film temperature via thermal convection, the grain size is remarkably reduced (Figure S8). These results imply that expediting the conversion of intermediates into perovskite is crucial for achieving large‐sized polycrystals [19,39] . The X‐ray diffraction (XRD) spectra of the three samples are summarized in Figure 3d, which exhibit a similar profile with two main diffraction peaks around 14.7° and 29.1°, as is characteristic of the tetragonal phase of CH 3 NH 3 PbI 3 polycrystals.…”
Section: Resultsmentioning
confidence: 85%
“…These results imply that expediting the conversion of intermediates into perovskite is crucial for achieving large-sized polycrystals. [19,39] The X-ray diffraction (XRD) spectra of the three samples are summarized in Figure 3d, which exhibit a similar profile with two main diffraction peaks around 14.7°and 29.1°, as is characteristic of the tetragonal phase of CH 3 NH 3 PbI 3 polycrystals. Nonetheless, as seen in Figure 3e, the full width at half-maximum (FWHM) of the 14.7°peak is reduced for the high-temperature annealed and the TU-treated films, in line with their large grain size.…”
Section: Chemphyschemmentioning
confidence: 82%
“…Additive engineering has been extensively used to regulate perovskite crystallization and defects passivation. For example, Liang et al introduced 1,8-diiodooctane (DIO) into perovskite precursor solution to regulate the kinetics of perovskite grains growth through coordinating with Pb 2+ in perovskite during crystallization . Correspondingly, a smoother and more continuous surface of perovskite grains was fabricated compared with that obtained from the pristine solution.…”
Section: Introductionmentioning
confidence: 99%
“…23−25 In many cases, they contain both a cation and an anion part with each playing a different role. Cations like ammonium (−NH to passivate negative defects by electrostatic interactions 26 or can be embedded into the perovskite lattice to form lowdimensional perovskites. 27,28 Anions like SCN − play an important role in overcoming growth challenges and reducing halide vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the small molecular additives possessing a single function, a variety of bifunctional or multiple functional additives have been reported recently. In many cases, they contain both a cation and an anion part with each playing a different role. Cations like ammonium (−NH 3 + ) groups tend to passivate negative defects by electrostatic interactions or can be embedded into the perovskite lattice to form low-dimensional perovskites. , Anions like SCN – play an important role in overcoming growth challenges and reducing halide vacancies . Moreover, it is found that single molecules can also provide synergistic effects.…”
Section: Introductionmentioning
confidence: 99%